2006
DOI: 10.1002/mds.21033
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations in the basal ganglia under normal conditions and in movement disorders

Abstract: A substantial body of work within the last decade has demonstrated that there is a variety of oscillatory phenomena that occur in the basal ganglia and in associated regions of the thalamus and cortex. Most of the earlier studies focused on recordings in rodents and primates. More recently, significant advances have been made in this field of research through the analysis of basal ganglia field potentials recorded from implanted deep brain stimulation electrodes in the basal ganglia of human patients with Park… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
168
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 293 publications
(185 citation statements)
references
References 156 publications
13
168
1
1
Order By: Relevance
“…Among these, abnormal bursting and oscillatory fluctuations of neuronal discharge are particularly noticeable [147][148][149][150][151][152]. Oscillatory activity can be identified in electrophysiological recordings of the activity of single neurons in GPi, SNr, STN, and MC in animals and patients with PD [153].…”
Section: Pathophysiology Of Parkinsonism and Dystoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, abnormal bursting and oscillatory fluctuations of neuronal discharge are particularly noticeable [147][148][149][150][151][152]. Oscillatory activity can be identified in electrophysiological recordings of the activity of single neurons in GPi, SNr, STN, and MC in animals and patients with PD [153].…”
Section: Pathophysiology Of Parkinsonism and Dystoniamentioning
confidence: 99%
“…In contrast, interventions directed at the PPN have revealed significant motoric effects in animal experiments [55]. Thus, PPN inactivation in normal primates reduces body movements of arms, trunk, and legs [142][143][144][145][146], and PPN injection of a GABA-A receptor antagonist, or low-frequency stimulation of PPN, alleviates experimental akinesia in monkeys, presumably by increasing PPN activity [146][147][148][149][150][151][152][153][154][155][156]. This constellation of findings suggests the possibility that the descending basal ganglia projections to the brainstem may play a greater role in the pathophysiology of akinesia/bradykinesia and movement than is commonly assumed.…”
Section: Pathophysiology Of Parkinsonism and Dystoniamentioning
confidence: 99%
“…In this regard, it is interesting to mention that an increase of NOS mRNA expression in the GP was observed in patients with Parkinson's disease (PD; Eve et al, 1998). Altered local level of NO could have effect on both the basal neuronal activity and the modulation of classical neurotransmission, leading to abnormal activity patterns in GPe neurons, such as bursty or synchronous rhythmic activity, which are thought to have far-reaching consequences for BG function and motor control (Bolam et al, 2000); moreover, altered synchronized and oscillatory activity of the GP/STN network, a central pacemaker likely responsible for synchronized oscillatory activity in the normal and pathological BG (Plenz and Kitai, 1999), could result in a less efficient coding of information by BG and, in turn, could contribute to the symptoms of Parkinson's disease (Gatev et al, 2006).…”
Section: Implication For Gp Function In Bg Circuitsmentioning
confidence: 99%
“…However, the mechanism by which stimulation at 100 -180 Hz has its therapeutic effects remains unclear. Work over the last decade has suggested that exaggerated synchronization of basal ganglia neurons may underpin Parkinsonian motor deficits (Gatev et al, 2006;Uhlhaas and Singer, 2006;Hammond et al, 2007) leading to the hypothesis that HFS may suppress pathological synchronization (Brown and Eusebio, 2008). In nonhuman primates made parkinsonian through injection of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, synchronization tends to occur at frequencies Ͻ15 Hz (Bergman et al, 1994;Nini et al, 1995), and extracellular recordings of neuronal discharges during HFS demonstrate a suppression of synchrony at these lower frequencies .…”
Section: Introductionmentioning
confidence: 99%